Digital Storytelling (DST) As Media In Teaching Speaking Skill - Muhammad Muklas; Jelita Jelita; Putri Rifani (Jurnal Pendidikan dan Sastra Inggris, 2023)
In this study, the writer took the title of research was “Digital Storytelling as Media in Teaching Speaking Skill”. It was conducted to find out whether any significant difference between students who are taught by using Digital Storytelling (DST) as media and the students who are taught by using conventional method in teaching students’ speaking skill at the seventh grade of SMP NU Tebat Jaya. This study used quantitative method, with quasi-experimental design. This study was collected performance test and analyzed with the independent t-test SPSS 21. The finding of this study showed that there is any significant difference between students in Experimental Class and students in Control Class. Therefore, Digital Storytelling (DST) media was suitable to be used in teaching students’ speaking skill at the seventh grade of SMP NU Tebat Jaya.